(untitled) (Baltic Journal of Sport and Health Sciences, 2024)
In this research, it is aimed to make carbon footprint measurements related to energy consumption (electricity, natural gas) in sports facilities belonging to public institutions in Ardahan province in Turkey. Afterwards, it is aimed to discuss the suggestions for minimising the footprint of the type and characteristics of the facilities in the light of current literature. This research is limited to Ardahan province and conducted as a case study. In this context, the amounts of electricity and natural gas consumed in 10 sports facilities with different types and characteristics located in Ardahan provincial centre and districts for 12 months during 2023 were used as a data set. Carbon footprint calculations caused by electricity and natural gas consumption from fossil resources in sports facilities were carried out within the scope of Scope 1. In addition, it is frequently used in carbon footprint calculations due to the ease of access to the amount of energy consumed within the scope of Scope 1 and relatively simpler data sets. The total carbon footprint due to the amount of electricity consumed in sports facilities is calculated as 173,467 tonnes, while the carbon footprint due to natural gas consumption is calculated as 511,578.21 tonnes. In 2023, the total carbon footprint caused by the amount of energy consumed in sports facilities for a year is 685,045.21 tonnes. In this research where Ardahan is considered within the scope of case study, the results of carbon footprint from sports facilities can be attributed to 2 main reasons. The first one is climate conditions. The second one is the increase in participation in amateur and professional events and organisations held in sports facilities and the intensive use of sports facilities throughout the 12 months. As a case study, minimising the carbon footprint of sports facilities in Ardahan province and reducing their negative environmental impacts are very important in terms of sustainable environmental goals. Keywords: carbon footprint, environment, sustainability, sports, sports facilitie.